STRATEGI GURU DALAM MENGEMBANGKAN MOTIVASI LITERASI BAHASA PADA SISWA DI SEKOLAH DASAR - Rahayu, Suci; Sukma, Elfia; Kharisma, Inggria (STKIP Subang, 2026)
Language literacy is a fundamental competence that supports students’ academic success, particularly at the elementary school level. Teachers play a strategic role in developing students’ language literacy motivation through appropriate and innovative learning strategies. This study aims to describe teachers’ strategies in enhancing language literacy motivation among elementary school students. The study employed a qualitative descriptive approach using a literature review method by analyzing various relevant national journal articles, books, and recent scientific references. The findings indicate that effective strategies include habituating daily reading activities, utilizing engaging learning media, implementing interactive learning, providing reading corners in classrooms, training writing skills gradually, and involving parents in literacy development. In addition, educational games, especially digital-based games, were found to increase students’ enthusiasm, participation, and interest in literacy learning. Positive reinforcement, such as praise and appreciation, also contributes to building students’ confidence and learning motivation. However, several challenges remain, including low reading interest, limited reading resources, excessive gadget use, and lack of parental support. Therefore, collaboration between teachers, schools, and families is essential to create a sustainable literacy culture. It can be concluded that teachers’ strategies significantly influence the development of students’ language literacy motivation and can help produce active, confident, and literate learners prepared for future educational challenges.